Position assessment of the tempo-mandibular joint condyle in patients with skeletal class II jaw relationship and distal occlusion - Drohomyretska, Мирослава Степанівна; Arshynnikov, Роман Сергійович; Polyanyk, Наталія Ярославівна; Ostryanko, Володимир Іванович; Tkachenko, Юлія Вячеславівна; Sukhomlynova, Тетяна Ярославівна (Actual Dentistry, 2023)
Resume. Modern orthodontic treatment requires an understanding of not only staticoc clusion, but also functional, including neuromuscular, and requires an individual approach to each clinical case. Therefore, our goal was to establish the frequency of various condyle positions for the future development of skeletal class II treatment protocols depending on the position of the constituent elements of the temporom ndibular joint. The ratio of patients who had bilateral central position of the articular process, bilateral anterior position, posterior position, patients who had unilateral central position, while the second articular process was displaced, was established. It has great importance for the treatment of patients with skeletal class II, which must depend not only on the horizontal and vertical direction of growth, the position of the teeth, but also on the position of the condyle of the lower jaw, which is very variable. Purpose. To evaluate the variability of various positions of the articular head for the future development of methods of treatment of skeletal class II depending on the position of the constituent elements of the TMJ.